Rooftop Rainwater Harvesting to Alleviate Domestic Water Shortage in the West Bank, Palestine - Sandy Alawna; Sameer Shadeed (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Water is a key factor for sustainable development which is in turn contributing to SDG 6 “Ensure access to water for all”. Generally, in arid and semi-arid regions, water is becoming less in quantity. This is due to the increasing water demand for different uses and the consequences of climate change. This situation compiled the urgent need to implement a sustainable and non-conventional water resources, among which is rooftop rainwater harvesting (RRWH) which is being studied in this research. This paper aims to estimate potential volume of RRWH and to evaluate the possibility of adopting RRWH as a reliable water resource in trying to bridge the domestic water supply-demand (DWSD) gap in the West Bank. The methodology of this study mainly rely on the use of the geographic information system (GIS) together with MS Excel. RRWH volumes were estimated based on the available GIS shapefiles of rooftops and long-term areal annual average rainfall. According to Palestinian Water Authority (PWA) data for the year 2017, the DWSD gap in the West Bank is 32 million cubic meters (MCM). In the West Bank, and given the vulnerable water supply, RRWH was found to be a strategic option to bridge this gap. The results of this study show that the estimated RRWH volume potentially available from West Bank rooftops is 37 MCM. Moreover, the adoption of RRWH in areas with high to very high domestic rainwater harvesting suitability can collect up to 32 MCM. Implementation of RRWH in high domestic water poor areas yet highly suitable for rainwater harvesting amounted to 53% of total RRWH volume in the West Bank. This paper may help potential Stakeholders (e.g. PWA) to adopt RRWH as a sustainable water resource option to alleviate domestic water shortage in the West Bank.